Chicken fat and inorganic nitrogen source for lipase production by Fusarium sp. (Gibberella fujikuroi complex) - Bruno, H. Oliveira [UNESP]; Nascimento, Valeria Marta Gomes do [UNESP] (Academic Journals, 2014)
In this work, we report the production of lipases by a Fusarium sp. isolate (FCLA-MA41) from Atlantic Forest, using chicken fat and association of organic and inorganic nitrogen sources in submerged fermentation to seek economically attractive bioprocess. A 2-level, 4-factor Central Composite Design (CCD) and response surface methodology (RSM) were used to study the influence of the concentrations of chicken fat, (NH4)2SO4, Triton X-100 and yeast extract as a nutrient supplement in Vogel minimum salt medium. RSM defined the region with the best response as consisting of the following combination of variables: chicken fat 15.0 mL/L, Triton X-100 15.0 g/L, ammonium sulfate 4.5 g/L and yeast extract 1.0 g/L. A validation study was performed according to the described concentrations and produced an enzymatic activity of 4.22 ± 0.35 U/mL. Considering the cost estimates of the nutrient medium optimized for lipase production, the production cost was $US 518.00/million Units of lipase.
Keywords: Fungal enzyme; Central composite design; Chicken fat; Ammonium sulfate; Triton X-100